Orchestrating the Tumor Microenvironment to Improve Survival for Patients With Pancreatic Cancer. Issue 4 (July 2015) - Whatcott, Clifford J.; Han, Haiyong; Von Hoff, Daniel D.
<x xml:space="preserve">Abstract</x> Abstract Pancreatic cancer is the fourth leading cause of cancer death in the United States. The microenvironment of pancreatic cancer could be one of the "perfect storms" that support the growth of a cancer. Indeed, pancreatic cancer may be the poster child of a problem with the microenvironment. In this article, we review the rationale and attempts to date on modifying or targeting structural proteins in the microenvironment including hyaluronan (HA) (in primary and metastases), collagen, and SPARC (secreted protein, acidic, and rich in cysteine). Indeed, working in this area has produced a regimen that improves survival for patients with advanced pancreatic cancer (nab-paclitaxel + gemcitabine). In addition, in initial clinical trials, PEGylated hyaluronidase appears promising. We also review a new approach that is different than targeting/destroying the microenvironment and that is orchestrating, reengineering, reprogramming, or normalizing the microenvironment (including normalizing structural proteins, normalizing an immunologically tumor-friendly environment to a less friendly environment, reversing epithelial-to-mesenchymal transition, and so on). We believe this will be most effectively done by agents that have global effects on transcription. There is initial evidence that this can be done by agents such as vitamin D derivatives and other new agents. There is no doubt these opportunities can now be tried in the clinic with hopefully beneficial effects.